Difficult Texts: Pronouns for God in Genesis 1.26, Exodus 20.2 and Isaiah 41.4–21 - Pugeda, Teofilo Giovan S, III (Archīum Ateneo, 2023)
This article explores using the third-person plural to refer to God as a Trinity. If this proves persuasive, the third-person plural may be an acceptable option to those hesitant about exclusively using male pronouns to refer to God and those wary of the politicization of pronouns.